Rola banku spółdzielczego w realizacji płatności elektronicznych - Garczyński, Dariusz (The Role of the Community Bank in Electronic Payment Accomplishment, 2005)
Community banking faces the big challenges connected with the fact that Poland has just joined the EU structures. The new situation forced banks to meet needs of the modem clients. Competitive market expects new products and services implementation and looking for the new distribution channels. Community banks seem to pay bigger attention to the electronic payments that belong to one of the electronic distribution areas. The proper service of the electronic payments may be an essential factor leading to the market superiority. The basic forms of the electronic payments, described in this paper, have been placed in the commercial offer of still growing up amount of community banks.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1068, s. 38-43